Description of a new genus, Chileana (Hymenoptera: Chalcidoidea: Torymidae), with four new species - Janšta, Petr; Křížková, Barbora; Vilímová, Jitka; Rasplus, Jean-Yves (Zootaxa, 2013)
Chileana Janšta & Křížková gen. nov. and four new species, C. cyanea Janšta & Křížková sp. nov., C. maculata Janšta & Křížková sp. nov., C. tricarinata Janšta & Křížková sp. nov. and C. penai Janšta & Křížková sp. nov., all from Chile, are described. The placement of this new genus within the tribe Monodontomerini is discussed and several characters suggest a close relationship to Zaglyptonotus.